Differential regulation of BACE1 expression by oxidative and nitrosative signals - Kwak, Young-Don (BioMed Central, 2011)
BACKGROUND: It is well established that both cerebral hypoperfusion/stroke and type 2 diabetes are risk factors for Alzheimer's disease (AD). Recently, the molecular link between ischemia/hypoxia and amyloid precursor protein (APP) processing has begun to be established. However, the role of the key common denominator, namely nitric oxide (NO), in AD is largely unknown. In this study, we investigated redox regulation of BACE1, the rate-limiting enzyme responsible for the β-cleavage of APP to Aβ peptides. RESULTS: Herein, we studied events such as S-nitrosylation, a covalent modification of cysteine residues by NO, and H(2)O(2)-mediated oxidation. We found that NO and H(2)O(2 )differentially modulate BACE1 expression and enzymatic activity: NO at low concentrations (<100 nM) suppresses BACE1 transcription as well as its enzymatic activity while at higher levels (0.1-100 μM) NO induces S-nitrosylation of BACE1 which inactivates the enzyme without altering its expression. Moreover, the suppressive effect on BACE1 transcription is mediated by the NO/cGMP-PKG signaling, likely through activated PGC-1α. H(2)O(2 )(1-10 μM) induces BACE1 expression via transcriptional activation, resulting in increased enzymatic activity. The differential effects of NO and H(2)O(2 )on BACE1 expression and activity are also reflected in their opposing effects on Aβ generation in cultured neurons in a dose-dependent manner. Furthermore, we found that BACE1 is highly S-nitrosylated in normal aging brains while S-nitrosylation is markedly reduced in AD brains. CONCLUSION: This study demonstrates for the first time that BACE1 is highly modified by NO via multiple mechanisms: low and high levels of NO suppress BACE1 via transcriptional and post translational regulation, in contrast with the upregulation of BACE1 by H(2)O(2)-mediated oxidation. These novel NO-mediated regulatory mechanisms likely protect BACE1 from being further oxidized by excessive oxidative stress, as from H(2)O(2 )and peroxynitrite which are known to upregulate BACE1 and activate the enzyme, resulting in excessive cleavage of APP and Aβ generation; they likely represent the crucial house-keeping mechanism for BACE1 expression/activation under physiological conditions.